2015
DOI: 10.5812/jjhs.26849v2
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of Vitamin C on Styrene-Induced Toxicity in Rat Liver and Kidney

Abstract: Background: Styrene (ST) is widely used as an organic solvent in many industrial settings. Increasing evidence indicated that ST induced toxicity in human and animals. Occupational exposure to ST can result in multiple-organ toxicity. Objectives: The aim of the present study was to investigate the preventive effect of vitamin C (Vit C) on ST-induced toxicity in rat liver and kidney. Materials and Methods: Adult male rats were pretreated with 300 mg/kg Vit C intraperitoneally. Control rats received vehicle only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…[22] In previous studies, the toxic effect of styrene on the liver of animal models has been reported. [23] Some of the styrene hepatotoxic effects are related to its transformation by hepatic enzymes. Styrene is metabolized in the liver and transformed into styrene oxide that is a toxic and potentially carcinogenic metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…[22] In previous studies, the toxic effect of styrene on the liver of animal models has been reported. [23] Some of the styrene hepatotoxic effects are related to its transformation by hepatic enzymes. Styrene is metabolized in the liver and transformed into styrene oxide that is a toxic and potentially carcinogenic metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…All these changes were neutralized when Vitamin E acetate cosupplemented with L-thyroxine. There are reports that Vitamin E acts as an antioxidant and improve the histology of male rat liver and kidney following cadmium-induced toxicity [57]. Sajitha et al [58] also reported that administration of Vitamin E has protected the histopathological and biochemical alterations induced by lead (Pb) intoxication in female Sprague-Dawley albino rats.…”
Section: Discussionmentioning
confidence: 99%
“…Styrene monomer has been reported to be carcinogenic [7] and can cause various forms of damages to many tissues including the liver and kidneys [8], neuronal cells [9], and cochlear [10,11]. Although styrene monomer has been reported to markedly affect many tissues, little is known regarding its toxicity in skeletal muscle tissue.…”
Section: Introductionmentioning
confidence: 99%